Prasasti Dalung Kuripan; Dokumentasi Perjanjian Banten – Lampung Tahun 1552 M - Hakiki, Kiki Muhamad; Effendi, Effendi; Badruzaman, Badruzaman; Badi’ah, Siti; Musofa, Ade (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research focuses on studying the Dalung Kuripna inscription manuscript. From the research facts, it can be concluded that the Dalung Kuripan inscription is a form of agreement between the Sultanate of Banten and Keratuan Darah Putih. This inscription is made with the background of three factors; First, economic factors. The Sultanate of Banten at that time became a supplier of spices, especially pepper to travelers and traders from various countries and Lampung was the largest supplier of pepper at that time, reaching 80%. On that basis, it is important for the Sultanate of Banten to approach and maintain good relations with local rulers or traditional stakeholders in the Lampung region. In order to maintain this good relationship, an agreement was made between Banten and Lampung, and the birth of the Dalung Kuripan inscription agreement. Second, political factors. The natural fertility of Lampung and the condition of local government that had not been centralized in one kingdom or power made Lampung easily controlled by either colonial or colonial nations such as the Netherlands, as well as by large kingdoms around the Lampung region including the Sriwijaya Kingdom. This condition made the Sultanate of Banten have an ambition to make Lampung in the territory of the Kingdom of Banten. The third is the religious factor. The position of Banten, which at that time was also the center of Islamic religious education, felt it was also important to preach it to various areas in Banten's territory, including Lampung. In order for the process of spreading Islam quickly, the Sultanate of Banten sent many local Banten ulama to teach Islam in the Lampung region. Since then, the people of Lampung, who initially embraced a lot of animism, Hinduism and Buddhism, soon converted to Islam. And since then, to this day, Islam remains the majority religion adhered to by the people of Lampung.